The Effectiveness of the Science Experimental Guidebook on the Conceptual Understanding of Students with Learning Disabilities - Tülay Şenel Çoruhlu; Murat Pehlevan (Universitas Pendidikan Indonesia, 2021)
This study aimed to develop a science experiments guidebook (based on discussion method and enriched worksheet) for fourth grade mainstreamed students with learning disabilities and to investigate its effect on their conceptual understanding of the